Auditory hallucination in basilar occlusion: I heard it was the basilar. Issue 2 (11th December 2015) - Yap, Siew Mei; Wyse, Gerald; Higgins, J Nicholas P; O'Brien, Eoin; Cronin, Simon
Abstract : Acute basilar artery occlusion is a neurological emergency. Unlike anterior circulation stroke presenting with hemiparesis, the symptoms of basilar artery occlusion are challenging to recognise in the emergency setting. Basilar artery occlusion can rarely lead to ischaemia of the auditory pathways, resulting in bizarre, positive auditory hallucinations. Here, we report two cases of basilar artery occlusion presenting with positive auditory phenomena; in both cases the auditory phenomenon resolved upon arterial recanalisation. We discuss the phenomenology of this unusual and distinctive neurological symptom. Acute auditory hallucinosis in the setting of sudden vomiting, dizziness, visual disturbance or other posterior circulation symptoms should prompt emergency imaging of the basilar artery, to avoid a potentially devastating posterior circulation stroke.